2021
DOI: 10.15326/jcopdf.2021.0201
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Obstructive Pulmonary Disease Outcomes at Veterans Affairs Versus Non-Veterans Affairs Hospitals

Abstract: For personal use only. Permission required for all other uses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…Twenty-five included studies 8 , 11 , 12 , 14 16 , 19 22 , 24 , 25 , 27 , 28 , 30 , 32 , 33 , 35 , 37 , 39 – 44 met all our risk of bias criteria. These good quality studies were given more weight in our narrative synthesis than studies that did not meet one or more criterion.…”
Section: Resultsmentioning
confidence: 99%
“…Twenty-five included studies 8 , 11 , 12 , 14 16 , 19 22 , 24 , 25 , 27 , 28 , 30 , 32 , 33 , 35 , 37 , 39 – 44 met all our risk of bias criteria. These good quality studies were given more weight in our narrative synthesis than studies that did not meet one or more criterion.…”
Section: Resultsmentioning
confidence: 99%
“… 17 We found lower mortality for HF and stroke but not AMI in VA hospitals, while another study found lower mortality for AMI and HF in VA hospitals but did not include stroke in a study of adults aged 65 years and older. 13 That study included veterans and nonveterans in an earlier period, which may explain different findings. 8 …”
Section: Discussionmentioning
confidence: 96%
“… 5 , 6 , 7 , 8 Many of these prior studies were limited to older veterans using VA services and older patients using Medicare services, including many nonveterans, due to wide availability of Medicare data. 8 , 9 , 10 , 11 , 12 , 13 , 14 However, the veteran enrollee population is more male and has worse health status, greater disability, and lower incomes compared with the nonveteran population. 15 , 16 Moreover, younger veterans are typically not included in comparisons due to a lack of comprehensive data on non-VA use outside of Medicare, which reduces the generalizability of these comparisons.…”
Section: Introductionmentioning
confidence: 99%
“… 43 These initiatives likely explain the recent finding of lower rates for 30-day re-admissions following hospitalizations for COPD at VA relative to non-VA hospitals. 44 …”
Section: Physiological Outcomes and Interventions To Optimize Them In...mentioning
confidence: 99%